The ancient mortars and geomaterials of tower fortification of Nora (Pula, Sardinia, Italy) - Columbu, Stefano (2022)
The tower is located on a promontory on the south-western Gulf of Cagliari, near to the Coltellazzo island and the archaeological Punic-Roman of Nora. The first military settlement was probably present since the beginning of the fourteenth century. Surely the tower was active since 1607. Jorge Aleo (1680) mentions, calling Fortalleza Coltellaz. In the eighteenth century the building was engulfed in a fort, built in a period of six years (1722-1728) by engineer the Piedmont Antonio Felix de Vincenti. Later (in the nineteenth century) further work was carried out until the tower became a lighthouse. The tower was considered a tower de armas or vigorous, or for heavy defense, with a garrison of men under a commander. Being a watch tower, is in sight of the towers of Cala d'Ostia, San Macario and the Diavolo. The tower has a structure of a truncated cone, with a height of about 11 meters high and 12 meters in diameter at the base. Inside it has a double ribbed vaulted dome, supported by a central pillar. The aim of this research is were studying mortars and geomaterials used of the ashlars, for define: i) composition of ancient mortars with ratio binder/aggregate; ii) provenance of the raw materials used in the mixture of mortars; iii) alteration processes in progress on mortars and on geomaterials used in masonry. Through the analysis of the physical-mechanical properties, important evidences of chemical and physical decay were highlighted in the mortar of the plasters coating the tower and also in bedding mortars of ashlars of masonry. In some areas, where they are concentrated processes of physical disintegration, also as a result of dissolution of the carbonate matrix of the mortar, show scarce resistance physical-mechanical with consequent detachment from the masonry.